FAKTOR DEMOTIVASI PEMBELAJARAN BAHASA ARAB DALAM PERSPEKTIF SISWA MADRASAH - Islam, Asep Muhammad Saepul (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
Motivation plays important role in language learning. When the language learner’s motivation is decreasing then he is being in a demotivation stage. Several previous studies in reveal that demotivation could diminish the student achievement in language skill. The phenomenon of this demotivation is rising in Arabic language learning in Indonesia’s madrasa. Using qualitative method with short essay from 105 students of Madrasah Aliyah Negeri (MAN) Cianjur, this study shows two major factors that cause demotivation in Arabic learning: external and internal. Specific external factors come from: (1) complexity of Arabic language; (2) learning material and method; (3) learning facility and environment; and (4) teacher’s behavior and personality. While internal factor sources are: (1) basic skill and previous learning experience; (2) negative attitude to Arabic subject. These factors need to be considered by teacher and other stakeholder as basic reference to increase student’s motivation in Arabic learning.DOI: 10.15408/a.v2i1.1511